A Comparison of Principal Component Analysis and Maximum Likelihood Factor Analysis in Bank Health Ratio - Firdaus, Firdaus; Nugroho, Sigit; Widodo, Haryo (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2021)
The use of factor analysis methods to reduce variable dimensions is generally known and has been used in various disciplines. The two famous extraction methods of factor analysis are principal component analysis and maximum likelihood. This study aimed to compare both, principal component analysis and maximum likelihood. By their constructed matrix correlation, applied to bank financial ratios. The study is developed from an initial set of 22 ratios of healthy indexed banks. The use of bank financial data aims to identify the structure of the financial ratio of healthy indexed banks. There are 10 variables satisfying the criteria of factor analysis techniques to be considered in the analysis. Both principal component analysis and maximum likelihood suggest three factors that can be used to represent 10 variables.Keywords: factor analysis; principal component analysis; maximum likelihood; financial ratios; bank health.